Pengaruh Latihan Jump Box Dan Agility Ladder Drill Terhadap Quick Smash Bola Voli Ekstrakurikuler Smk Negeri 2 Palopo - Nanda Pertiwi; Rasyidah Jalil; Suaib Nur (Universitas Hamzanwadi, 2026)
The volleyball club students at SMK Negeri 2 Palopo still face difficulties in executing the quick smash technique effectively, due to limited mastery of basic techniques, a lack of understanding of explosive movements, and a shortage of speed- and agility-oriented training. This study aims to determine the effect of jump box and agility ladder drill exercises on the quick smash ability of the volleyball students in the extracurricular program at SMK Negeri 2 Palopo. The study used an experimental method with a one-group pretest-posttest design. The sample consisted of 20 male students selected through purposive sampling. The instrument consisted of a quick smash ability test evaluated by three expert judges using a 5-aspect scoring rubric. Training was conducted over 12 sessions spanning 4 weeks. Data analysis utilized the Paired Sample t-test after the data met the criteria for normality and homogeneity. The results showed an increase in the mean score from the pretest (14.25) to the posttest (18.45). The Paired Sample t-test yielded a t-value of 8.847 and a significance level of 0.000 (p < 0.05), indicating a significant effect. The conclusion is that jump box and agility ladder drills have a significant effect on improving quick smash ability and can be recommended as an alternative training program for volleyball coaches.